PENGARUH KUALITAS LAYANAN DAN PERSEPSI HARGA TERHADAP KEPUASAN PELANGGAN UNTUK MENINGKATKAN LOYALITAS PELANGGAN (Studi pada Pelanggan Susan Executive Club Semarang) - Saidatus Salamah, 14.05.51.0087; Tjahjaningsih, Endang (Students Journal of Economic and Management, 2018)
The purpose of this study is describing and analyzing the effect of Service Quality, Perceptions of Price of customer satisfaction, and the effect of customer satisfaction of customer loyalty. The population of this study is the customer of Susan Executive Club Semarang. The method of taking sampling is used purposive sampling method, and got 100 respondent sampling. The analysis method is used doubled linier regression. Based on the analysis can be concluded that there is significant effect of service quality variable to customer satisfaction, and significant affect of sevice quality variable to customer loyalty. There is significant effect of perceptions of price variable of customer satisfaction and customer loyalty. Mulberryâs effect of service quality variable and perceptions of price to customer satisfaction amount 53,001%, and the effect of service quality, perceptions of price, and customer satisfaction of customer loyalty is amount of 55,433%.Key word : service quality, perceptions of price, customer satisfaction and customer loyalty